THE INFLUENCE OF PRICE AND PRODUCT INNOVATION ON THE PURCHASE INTENTION OF WULING ELECTRIC CARS WITH BRAND IMAGE AS AN INTERVENING VARIABLE: A STUDY ON PROSPECTIVE ELECTRIC CAR CONSUMERS IN EAST JAVA - Rahmi Rahayu, Dita; Pratikto, Heri; Siswanto, Ely (IJBLE Scientific Publications Community Inc., 2023)
This research aims to examine the influence of price and product innovation on the purchase intention of Wuling electric cars through brand image among prospective Wuling electric car consumers in East Java. This study adopts a descriptive and explanatory research design with a quantitative approach. Structural Equation Modeling-Partial Least Squares (SEM-PLS) is used for data analysis. Survey questionnaires are collected through both online means using Google Forms and offline methods through the distribution of printed questionnaires. The sample size for this study comprises 217 prospective Wuling electric car consumers in East Java. The findings indicate that price and product innovation have a positive and significant impact on brand image. Moreover, brand image, price, and product innovation have a positive and significant effect on purchase intention, with brand image mediating the relationship between price, product innovation, and purchase intention. These results highlight the crucial role of brand image in mediating the effects of price, product innovation, and purchase intention among prospective Wuling electric car consumers. The implications of this research suggest that companies should continuously develop their brand image to enhance the sales of Wuling electric cars. Additionally, the study's findings can contribute to the advancement of marketing management knowledge